Kajian Semiotika Dalam Komunikasi Islam (Analisis Simbol, Makna, Dan Interpretasi Dalam Penyebaran Pesan Dakwah) - Solimin Solimin; Eko Carles; Nur Kholifah; Nova Dwiyanti (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to examine the role of symbols, meanings, and interpretation processes in Islamic communication, especially in the context of spreading da'wah messages. In the midst of the development of digital technology and globalization, da'wah messages are no longer delivered conventionally, but through visual symbols that contain layered aesthetic, cultural, and religious values. By referring to classical semiotic theories such as those proposed by Saussure and Peirce, this study utilizes a qualitative approach through case studies and content analysis of da'wah materials distributed in traditional and digital media. Analysis of religious symbols reveals the dynamics of the relationship between denotative and connotative meanings that have the potential to create a plurality of interpretations among the people. The results of the study indicate that differences in cultural context and adaptation of digital media also influence the perception of da'wah messages, thus requiring adaptive communication strategies that are sensitive to the dynamics of religious values. These findings are expected to provide theoretical and practical contributions in the development of more effective and inclusive da'wah message delivery methods.